Application Of Study Time Prediction Management Study Program Faculty Of Economics Dehasen University Bengkulu Using Naive Bayes Method - Dzaki Muhammad Alwan; Dewi Suranti; Rizka Tri Alinse (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The Management Study Program is one of the Strata 1 (S-1) study programs located at the Faculty of Economics, Dehasen University, Bengkulu. Students who graduate with a study period of 7 semesters to less than 8 semesters, 8 semesters and more than 8 semesters have different grades. The success of students completing their study period cannot be separated from the factor of the study plan prepared by the Head of the Study Program. The number of students who will conduct consultations on study plans, makes the study program overwhelmed and requires quite a lot of time to help provide information on the future of study. Therefore, we need a system that can help provide recommendations for predicting the results of the study period for each student automatically. The application for predicting the study period of students in the Management Study Program, Faculty of Economics, University of Dehasen Bengkulu, was created to help provide recommendations for predicting study period results for each student automatically by applying the Naive Bayes Method. The classification is divided into 3 parts, namely students who graduate early (7 semesters to less than 8 semesters), students who graduate on time (8 semesters) and students who graduate not on time (more than 8 semesters). Based on student grade data in 2019, the results of the prediction for the study period of 30 students were obtained, namely 22 people graduating faster, 2 people graduating on time, and 6 people graduating not on time..